Relationship between self-disclosure and anticipatory grief in patients with advanced lung cancer: the mediation role of illness uncertainty - Zhang, Nan; Li, Han; Kang, Huaxin; Wang, Yinglan; Zuo, Zhitong (Frontiers in Psychology, 2023)
To study the relationship between self-disclosure, illness uncertainty(IU)and anticipatory grief(AG) in patients with advanced lung cancer. Methods: This is a cross-sectional study using convenience sampling method, in which 316 patients with advanced lung cancer who were hospitalized in a tertiary hospital in Wuxi City, China, from November 2022 to April 2023 were sampled. The Preparatory Grief in Advanced Cancer Patients , Mishel Uncertainty in Illness Scale, and the Distress Disclosure Index Scale (DDI) were selected to analyse the status quo, correlations, and the mediating effect of illness uncertainty on the relationship between self-disclosure and anticipatory grief in advanced lung cancer patients. Results: The total self-disclosure score of advanced lung cancer patients was (36.35±9.25), the total score of IU was (56.92±15.65), and the score of AG was (52.29±9.08); the results of correlation analyses showed that IU was negatively correlated with self-disclosure in advanced lung cancer patients (P<0.05) and positively correlated with AG (P< 0.05), and self-disclosure was negatively correlated with AG (P<0.05);the mediating effect rate of IU between selfdisclosure and AG in advanced lung cancer patients was 49%.The AG of advanced lung cancer patients was at a medium-high level, and IU had a significant mediating effect between self-disclosure and AG of advanced lung cancer patients; by increasing the level of patients' self-disclosure, IU could be effectively alleviated, and ultimately the AG of the patients could be reduced. Keywords:lung cancer,anticipatory grief,illness uncertainty,self-disclosure, structural equation model INTRODUCTION According to cancer statistics released in the United States, lung cancer has become the second most prevalent cancer, but it still occupies the top spot for cancer deaths over 50 years of age (Siegel et al., 2023). The World Health Organisation's International Agency for Research on Cancer (IARC) recently released the latest global cancer burden data for 2020, and China ranked first in the world in terms of the number of new cases and deaths, with the number of new cancers reaching as high as 4.57 million, accounting for 23.7 per cent of the total global cancer mortality rate (Sung et al., 2021). In China, the